Multilingualism And Asean Single Market: In The Perspective Of International Trade Facilitations - Ika Riswanti Putranti (Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The European Union is a successful common market role model through regional economic integration. The formation of common market by several countries within a country brings widespread implications not only in economic and legal aspects but also socially and culturally. There are four basic principles in the formation of a common European Union market of freedom of movement of goods, freedom of movement of services, freedom of movement of capital, freedom of movement of people. The application of the four principles within the framework of economic integration is strongly influenced by the social and cultural interactions taking place within the market structure. The part of culture is an essential element in doing economic interaction is the language. Multilingualism in the EU affects common market dynamics and policy patterns in trade facilitation.